2022
DOI: 10.3389/fimmu.2022.941880
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to induce natural killer cell tolerance in xenotransplantation

Abstract: Eliminating major xenoantigens in pig cells has drastically reduced human antibody-mediated hyperacute xenograft rejection (HXR). Despite these advancements, acute xenograft rejection (AXR) remains one of the major obstacles to clinical xenotransplantation, mediated by innate immune cells, including macrophages, neutrophils, and natural killer (NK) cells. NK cells play an ‘effector’ role by releasing cytotoxicity granules against xenogeneic cells and an ‘affecter’ role on other immune cells through cytokine se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…Expressing inhibitory ligands on porcine cells to induce human NK cell tolerance is a practical approach to protect xenografts from human NK cell-mediated destruction ( 43 ). We showed that co-expressing HLA-E and HLA-G on a genetically modified 5GKO cell line synergistically reduced human NK cell activation as compared to cells expressing either HLA-E or HLA-G alone as well as 5GKO parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Expressing inhibitory ligands on porcine cells to induce human NK cell tolerance is a practical approach to protect xenografts from human NK cell-mediated destruction ( 43 ). We showed that co-expressing HLA-E and HLA-G on a genetically modified 5GKO cell line synergistically reduced human NK cell activation as compared to cells expressing either HLA-E or HLA-G alone as well as 5GKO parental cells.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will focus on identifying and eliminating porcine ligands for human NKG2D receptor from porcine cells, as well as introducing HLA-E and HLA-G inhibitory ligands into porcine cells through genetic engineering. These strategies have great potential to block human NK cell activation and NK cell-mediated rejection [38]. Additionally, investigating the interplay between NK cells and other immune cell populations, such as macrophages and T cells, could provide a more comprehensive understanding of the immune response to xenogeneic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we are just scratching the surface of the iceberg about the function and mechanisms of each type of cells. For instance, NK cells may play an effector role by releasing cytotoxicity granules against xenogeneic cells, or an affector role on other immune cells through cytokine secretion ( 117 ), and much work need to be carried out to promote xenograft acceptance by driving NK cells ( 118 ).…”
Section: Research Interestsmentioning
confidence: 99%